PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, PERAN AUDIT INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada OPD Kabupaten Sukoharjo) - Handayani, Putri Nur; Rispantyo, Rispantyo; Sunarti, Sunarti (Universitas Slamet Riyadi, 2020)
This study aims to determine the effect of application of government accounting standards on quality of region’s government financial reports, the effect of human resource competencies on quality of regions’s government financial reports, the effect of the role of internal audit on quality of regin’s government financial reports, and to determine the effect of the application of government accounting standards, human resources, the role of internal audits on the quality of region’s government financial reports. This study belongs to quantitative research. The sample was determined by purposive sampling technique used 161 sample. Data analysis was done by using multiple regression with the help of SPSS V21 software. The results showed that the application of government accounting standards had a positive and significant effect on the quality of region’s government financial report, human resource competence had a positive and significant effect on the quality of region’s government financial reports, the role of internal audit had a positive and significant effect on the quality of region’s government financial reports, and the application of government accounting standards, human resource competencies, the role of internal audit had a significant effect on the quality of region’s government financial reports.